Co-teaching with English language newcomers in a middle school science class - Havermann, Jenny Lee Green (My University, 2024)
The purpose of this qualitative case study was to investigate how a Title 1 middle school with ~12% EL population transitions from a push-in (1 teach, 1 assist) co-teach model to a collaborative (team teaching) co-teach model of instruction with EL Newcomers during an academic semester. The research study aimed to understand how two middle school science educators implemented a co-teach program model with EL Newcomers, what the perceived impact to their professional identity was during implementation, and how the educators developed a co-teach partnership during the semester. Co-teaching was the backdrop for this qualitative case study, but it was focused by symbolic interactionism and teacher’s professional identity. Symbolic interactionism provided the lens for understanding how the two participants made meaning out of their interactions. This meaning-making then influenced changes to each teacher’s professional identity and the co-teach team identity that formed. In addition to examining the formation and changes to each teacher’s professional identity, this case study also followed the journey of two educators, who are both science educators and one is also ESOL certified, as they became a collaborative co-teaching team. This journey is documented during recorded interviews, classroom observations, and co-planning meeting observations. In reviewing and analyzing the data the following four themes were observed: • Teacher identity • Necessary traits for collaboration • Team goals • Team identity These four themes, along with the observational data, help explain how the two educators could go from using mainly a 1 teach, 1 assist (1T, 1A) co-teach strategy to team teaching (TT) strategy. The findings from the study suggest the journey of the two educators from viewing themselves as individuals working in the same classroom to calling themselves a team and viewing themselves as the coaches was possible because of the relationship they were able to develop with each other during their interactions. Symbolic interactionism suggests that without interactions, individuals are not able to make meaning or gain understanding of the person they are working with. Without the opportunity to collaborate, for instance during their co-planning meetings, these two educators may not have made the journey to team teaching. As the two educators began their switch from 1T, 1A to TT, they began to develop lessons that were differentiated and modified for all levels of students, including EL Newcomers. Throughout this case study, the following question has been the focus and guiding the way: How do middle school science educators implement a co-teach model of instruction with EL Newcomers?
Keywords: EL Newcomers; Secondary education; Co-teaching; Science; Middle school